1998
DOI: 10.1002/(sici)1097-4628(19981226)70:13<2695::aid-app14>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Polymer blends by self-propagating frontal polymerization

Abstract: ABSTRACT:The use of self-propagating frontal polymerization to produce polymer blends has been investigated. A homogeneous solution of monomer, polymer (of a second monomer), and initiator is initially heated at a specific location to start a polymerization front that propagates along the system. The obtained polymerization reaction is very fast compared with diffusion, so that the two types of macromolecules remain homogeneously distributed, as in the original monomer/polymer solution. In the case of two inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Although frontal polymerization dates back to the 70 s (46) and has been employed in engineering, chemistry, and astrophysics (47)(48)(49), its use in drug delivery is recent (30). Frontal polymerization is a process of polymerization whereby the reaction is initiated from one end of the sample and then it propagates throughout the sample.…”
Section: Frontal Polymerization For Hydrogelsmentioning
confidence: 99%
“…Although frontal polymerization dates back to the 70 s (46) and has been employed in engineering, chemistry, and astrophysics (47)(48)(49), its use in drug delivery is recent (30). Frontal polymerization is a process of polymerization whereby the reaction is initiated from one end of the sample and then it propagates throughout the sample.…”
Section: Frontal Polymerization For Hydrogelsmentioning
confidence: 99%
“…Since the nineties, a great deal of work has been done mainly by Pojman et al who studied macrokinetics and dynamics [8][9][10][11][12] and new frontally polymerizing systems [13][14][15]; Morbidelli et al suggested the application of FP to the preparation of copolymers [16] and blends [17]; Washington and Steinbock published on the preparation of hydrogels by FP [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Zhai et al, and Koike and Zhang et al have demonstrated the synthesis of gradient refractive index (GRIN) material by isothermal FP [26][27][28]. FP has also been used to cure mortar composition [29], synthesize copolymers [30], hydrogels [31], polymer-dispersed liquid crystals [33], homogeneous polymer blends [34], and crosslinked functional polymers [35].…”
Section: Introductionmentioning
confidence: 99%